2019
DOI: 10.1016/j.ijnss.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in self-care maintenance and its associations among patients with chronic heart failure

Abstract: Objectives To identify the gender differences in self-care maintenance and its associations among chronic heart failure patients using the Information-Motivation-Behavioral Skills model. Methods Two hundred and ten patients (54.0% female) with chronic heart failure participated in this cross-sectional study. Self-care, knowledge of heart failure, social support and illness perception were measured using the Self-Care of Heart Failure Index, the questionnaire of heart fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 42 publications
5
29
0
Order By: Relevance
“…Women adhered more strictly to good dietary habits compared to men. This finding is consistent with those of previous studies [ 48 , 49 ], which revealed that women had better adherence to health-promoting behaviors than men. Traditionally, shopping for ingredients and preparing meals is a domestic role for women [ 50 ], so women are more responsible for cooking and preparing meals.…”
Section: Discussionsupporting
confidence: 94%
“…Women adhered more strictly to good dietary habits compared to men. This finding is consistent with those of previous studies [ 48 , 49 ], which revealed that women had better adherence to health-promoting behaviors than men. Traditionally, shopping for ingredients and preparing meals is a domestic role for women [ 50 ], so women are more responsible for cooking and preparing meals.…”
Section: Discussionsupporting
confidence: 94%
“…Finally, the results regarding known-groups validity showed that the LW-CI-HF scale discriminates depending on marital status, employment situation or the severity of HF according to the NYHA classification and PGIS [ 48 , 49 , 50 ]. We know that HF produces a considerable disruption in patients’ marital and working lives, and these variables are important determinants of clinical outcomes in HF [ 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Internal validity, defined as the intercorrelations between the LW-CI-HF scale dimensions (standard, r s = 0.3−0.7) [ 36 , 38 ] was also tested. Known-group validity of the LW-CI-HF scale was analysed in the sample grouped by sociodemographic data, functional classification according to the NYHA classification and PGIS scores [ 48 , 49 , 50 ]. Hypotheses related to significant differences in LW-CI-HF scores by gender, marital status, employment situation, NYHA classification and PGIS levels were set, following the literature [ 49 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations